Views of Elementary School Teachers and Slovenian Language Teachers on Interpretive Reading - Petek, Tomaž (Revija za elementarno izobraževanje, 2024)
The basis for modern planning of literature teaching is communication teaching. In the present study, we assumed that interpretive reading by the teacher plays a central role in the recommended model of school interpretation of literary texts for the development of student reading ability. We investigated the views of elementary school teachers and Slovenian language teachers on interpretive reading. A survey of 110 teachers revealed, among other things, that most consider appropriate interpretive reading in the classroom to be very important and that knowledge about it should be further developed. There was no difference between elementary school teachers and Slovenian language teachers in terms of knowledge about interpretive reading.
Keywords: communication teaching, school-based interpreting, literary texts, interpretive reading, teachers' views.